I'm stuck on proving this statement below due to that I can't seem to find a base case that is true:

Prove that $$\sum_{i=0}^{2n}(-1)^if(i) = f(0) - f(1) + f(2) - \cdots - f(2n-1) + f(2n) = f(2n-1)-1,$$ where $f(i)$ is the $i$th Fibonacci number.

I believe simple induction should work but I am unsure if I have to use Strong Induction.


marked as duplicate by lulu, Namaste discrete-mathematics Mar 21 '17 at 0:08

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

  • $\begingroup$ For what $n$ do you need to prove this? $\endgroup$ – Mastrem Mar 20 '17 at 20:09
  • $\begingroup$ The sum looks like it should be $\sum (-1)^iF(i)$ not $F(2i)$. $\endgroup$ – Mark Fischler Mar 20 '17 at 20:11
  • $\begingroup$ why you are "unsure" about using weak or strong induction? Just try the weak induction approach, if it gets complicate try the other. So you dont need to be unsure! $\endgroup$ – Masacroso Mar 20 '17 at 20:12

For $n+1$ we have

$$\sum_{i=0}^{2(n+1)}(-1)^if(i)=\sum_{i=0}^{2n}(-1)^if(i)-f(2n+1)+f(2n+2)=\\ =f(2n-1)-1-f(2n+1)+f(2n+2)$$


$$f(2n+2)=f(2n+1)+f(2n),\\ f(2n+1)=f(2n)+f(2n-1)$$ so,


and then



Not the answer you're looking for? Browse other questions tagged or ask your own question.